2015
DOI: 10.2196/mhealth.4183
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Using Mobile Phone Image Capture for Collecting Secondary Data: A Case Study on Immunization History Data Among Children in Remote Areas of Thailand

Abstract: BackgroundEntering data onto paper-based forms, then digitizing them, is a traditional data-management method that might result in poor data quality, especially when the secondary data are incomplete, illegible, or missing. Transcription errors from source documents to case report forms (CRFs) are common, and subsequently the errors pass from the CRFs to the electronic database.ObjectiveThis study aimed to demonstrate the usefulness and to evaluate the effectiveness of mobile phone camera applications in captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…They also addressed gaps in patient-physician communication arising from patients’ inability to promptly reach a physician and difficulty understanding their physician’s medical advice [ 28 , 29 ]. Data collection applications aimed to minimize errors associated with traditional lengthy paper-based data collection methods [ 30 , 31 ], and the time required to train poorly educated CHWs [ 32 ]. Telemedicine solutions intended to deliver care to remote locations by overcoming time constraints, transportation difficulties, travel distance, and costs [ 2 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also addressed gaps in patient-physician communication arising from patients’ inability to promptly reach a physician and difficulty understanding their physician’s medical advice [ 28 , 29 ]. Data collection applications aimed to minimize errors associated with traditional lengthy paper-based data collection methods [ 30 , 31 ], and the time required to train poorly educated CHWs [ 32 ]. Telemedicine solutions intended to deliver care to remote locations by overcoming time constraints, transportation difficulties, travel distance, and costs [ 2 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the data collection area, all studies were app solutions, with four out of six located in LMICs and led by healthcare providers. VHVs in Thailand increased data quality and completeness by using the mobile camera application to capture images of the mothers’ logbooks and record immunization data [ 30 ]. In the CommCare study [ 32 ], CHWs’ training time considerably dropped as they used a mobile app to calculate CVD risk and limit the errors that resulted from paper charts.…”
Section: Resultsmentioning
confidence: 99%
“…24 A recent study in a resource-limited setting also revealed that in comparison with records from written health logbooks, the direct capture of data from the source documents by using mobile devices led to higher reported immunization coverage among children. 25 Thus, the use of electronic records, direct data capture, and biometric validation during recruitment and follow-up visits may have contributed to the nonsignificant increase (8%) in the immunization coverage observed in the control group merely from better record keeping. This is supported by the fact that 18% of the subjects in this study did not have any written immunization record at the time of recruitment.…”
Section: Figurementioning
confidence: 99%
“…"Parents" in this paper refer to all primary caregivers. In Thailand, the maternal and child health handbook (MCHH) is the medium to facilitate preventive health care communication between parents and the child's health care provider [3][4][5].…”
Section: Introductionmentioning
confidence: 99%